Antibody responses to flagellin C and Streptococcus gallolyticus pilus proteins in colorectal cancer - Butt, Julia; Larrea, Nerea Fernández de; Tjalsma, Harold (Scientific reports, 2019)
Antibodies to Streptococcus gallolyticus subspecies gallolyticus (SGG) have been associated with colorectal cancer (CRC). Because SGG may correlate with impaired gut epithelia, we assessed the association of antibodies to bacterial flagellin C (FliC), a measure potentially related to this impairment, with CRC and the CRC-specific interaction with antibodies to SGG proteins. Antibodies to FliC and SGG pilus proteins Gallo2178 and Gallo2179 were measured in two independent studies, a combined study from Nijmegen and Detroit (93 CRC cases, 74 controls) and a replication data set including 576 cases and 576 controls from the Spanish multicenter multicase-control study (MCC-Spain). Logistic regression was applied to assess whether antibodies to FliC were associated with CRC and modified the association of antibodies to SGG proteins with CRC. Antibodies to FliC were associated with those to SGG Gallo2178 among CRC cases, resulting in an interaction in the association of antibodies to Gallo2178 with CRC (p = 0.007). This association was only present among individuals with high antibody responses to FliC (OR: 2.42, 95% CI: 1.45-4.06). In conclusion, our findings suggest that colorectal tumorigenesis could be accompanied by an impaired integrity of the epithelium that could result in associated increased antibody responses to bacterial proteins.
Gesehen am 30.10.2019